PENGARUH MINAT KONSUMEN TERHADAP LAYANAN PURNA JUAL PADA PENERBANGAN LOW COST CARRIER - Amrina Rosada; Ahmad Musadek; Siti Fatimah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
The influence of consumer interest in after-sales service for online tickets on Low Cost Carrier (LCC) flights is a unique flight model with a strategy to reduce operating costs. Carry out cost efficiency on all fronts so that airlines can offer low cost flight services. This research will measure customer assessment of service quality and price variables on user satisfaction of low cost carrier services in Indonesia. Respondents of this study were 50 people who have used 3 low cost carrier airlines, namely Lion Air, AirAsia, and Sriwijaya Air, where the three airlines have around 72% market share. The sampling technique used was convenience sampling by distributing questionnaires to respondents. The data analysis technique in this study uses Statistikal Package for the Social Sciens (SPSS). Based on the results of data processing, it is known that service quality is more influential than price on satisfaction. Both service quality and price have the same positive and significant effect.